2018
DOI: 10.1038/s41598-018-32580-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fingerprinting of nanoparticles in complex media with non-contact photoacoustics: beyond the light scattering limit

Abstract: Optical instruments can probe physical systems even to the level of individual molecules. In particular, every molecule, solution, and structure such as a living cell has a unique absorption spectrum representing a molecular fingerprint. This spectrum can help identify a particular molecule from others or quantify its concentration; however, scattering limits molecular fingerprinting within a complex compound and must be overcome. Here, we present a new, non-contact photoacoustic (PA)-based method that can alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 74 publications
1
14
1
Order By: Relevance
“…Other PA spectrometers based on dedicated single-element detectors place fewer constraints related to the ultrasound frequency response of the detector. They evaluate the optical absorption coefficient using calibration with a known reference solution [12,13]. For these PA spectrometers, small sample volumes (3 µL [13] and 200 µL [12]) are placed in optically transparent cells, and SPP is performed on the same sample to concurrently measure the optical attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…Other PA spectrometers based on dedicated single-element detectors place fewer constraints related to the ultrasound frequency response of the detector. They evaluate the optical absorption coefficient using calibration with a known reference solution [12,13]. For these PA spectrometers, small sample volumes (3 µL [13] and 200 µL [12]) are placed in optically transparent cells, and SPP is performed on the same sample to concurrently measure the optical attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption spectra measured by UV-Vis were also strongly influenced by the biological medium; in the complex media, the samples exhibited significant scattering increase (compared to in UPW) and a second peak, revealing the presence of proteins in the sample. These results can be related to the fact that a considerable fraction of transmitted light does not reach the UV-Vis detector due to the complex nature of the cell medium, recording a higher absorption for these samples [41].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional piezoelectric transducers limit the potential axial resolution of broadband PA signals. Note that all-optical detectors of PA signal are wideband and have significant advantage in these terms [22,23].…”
Section: Photoacoustic Imagingmentioning
confidence: 99%
“…Petrova et al [55] demonstrated that generation of PA response from blood in terms of its thermoelastic properties depends on compartmentalization of hemoglobin within erythrocyte. Recently, Pelivanov et al [22] showed that localization of nanoagents in extracellular and/or intracellular matrix can affect the resultant absorption spectrum of nanoagents (Figure 8).…”
Section: Identifying Photoacoustic Properties Of Target Nanoagents Inmentioning
confidence: 99%
See 1 more Smart Citation